Greenhouse governance : addressing climate change in America - Rabe, Barry George, 1957- (Brookings Institution Press, 2010)
"Examines national and international laws and institutions governing human-mediated climate change. Issues examined include public perceptions and economic effects of climate change and policies to mitigate it, renewable electricity standards, vehicle fuel economy standards, cap-and-trade regimes, carbon taxes, and the adaptation-versus-mitigation debate"--Provided by publisher.